Topographic lymph node staging system shows prognostic superiority compared to the 8th edition of AJCC TNM in gastric cancer. A western monocentric experience. (September 2020) - Lauricella, S.; Caricato, M.; Mascianà, G.; Carannante, F.; Carnazza, M.; Bonaccorso, A.; Angeletti, S.; Ciccozzi, M.; Coppola, R.; Capolupo, G.T.
Abstract: Introduction: The current Tumor Node Metastasis staging system (TNM) for gastric cancer classifies the extent of lymph node metastasis based upon the number of lymph nodes involved. Choi et al. have recently proposed a new anatomical classification based upon the regionality of the involved nodes. This new classification seems to have a better predictive prognostic value than the traditional one. We investigated the prognostic role of the new anatomical based classification, reviewing our institutional gastric cancer database. Methods: We performed a retrospective chart review of 329 patients who underwent gastrectomy at our Institution from 2003 to 2017. We excluded from data analysis any patient with distant metastases at the time of first diagnosis and or surgery, pathology other than adenocarcinoma, lymphadenectomy less than D2, impossibility to identify location of lymph nodes (LNs) on pathological report and neoadjuvant chemotherapy. The extent of D2 lymphadenectomy was defined according to Japanese Gastric Cancer Association criteria. LN metastasis were reclassified into three topographic groups (lesser, greater curvature, and extraperigastric nodes) and staged according to Choi. The new N stage was combined with the current pT according to the 8th edition of TNM and a new hybrid TNM stage was established. All patients were followed up until June 2019. The prognostic performance of the new stage and of the current anatomical numeric based system (TNM) was analyzed and assessed by the C-index, AIC and likelihood ratio χ 2 value. Results: In predicting both Overall Survival (OS) and Disease free Survival (DFS) the new N stage and the new TNM staging system had the highest C-index and likelihood ratio χ2 value and the lowest Akaike Information Criterion (AIC), showing a better accuracy and displaying a better prognostic performance. Conclusions: Our study is the first from the Western world to compare the new hybrid classification, based on the anatomical location of metastatic nodes, to the 8th of American Joint Committee on Cancer (AJCC) TNM staging system. Our findings on a small, monocentric sample suggest that hybrid topographic lymph node staging system is more accurate than TNM. Highlights: Gastric cancer is the third most common cause of cancer death worldwide. We proposed a new anatomical nodal staging system for gastric cancer patients. Patients undergoing surgery were reclassified according to the new classification. The prognostic performance of the new stage was analyzed. Hybrid topographic lymph node staging system shows a better prognostic performance.